OD ŚWIATÓW WIRTUALNYCH DO MEDIÓW SPOŁECZNOŚCIOWYCH – O INNOWACYJNYM WYKORZYSTANIU INTERNETOWYCH PLATFORM GLOTTODYDAKTYCZNYCH W KSZTAŁCENIU NEOFILOLOGICZNYM - Krajka, Jarosław (Neofilolog, 2018)
Using various forms of computer-assisted instruction in foreign language teacher and translator training has become an obvious fact. While fully distance programs are rather scarce, more and more projects adopt the blended learning approach mediated by different webbased tools. The purpose of the paper is to critically describe and analyse a myriad of tools used as e-learning platforms: Learning Management Systems, glottodidactic platforms, virtual worlds, wikis and social networking tools. It is essential to see different dimensions of innovation in language teacher and translator training, in terms of technology, course management and task design. The discussion will be based on examples of projects run through the tools under analysis in different university programmes all over Poland.